Imbalance in Teacher Readiness Between Technological Self-Efficacy and Ethical Awareness in the Era of AI Humanification - Pande Ni Putu Vania Dharmapatni; Made Hery Santosa; Anak Agung Gede Yudha Paramartha (Jurnal Studi Guru dan Pembelajaran, 2026)
The development of Generative Artificial Intelligence (GenAI) has transformed assessment practices in English as a Foreign Language (EFL) learning, particularly through the emergence of AI humanification, where the boundaries between authentic student writing and AI-generated text become increasingly blurred. This study aims to analyze secondary school English teachers’ readiness in addressing these challenges. This research employed a sequential explanatory mixed-method design involving 23 EFL teachers from nine senior high schools in Buleleng Regency, selected through purposive sampling. Data were collected using a modified Readiness Artificial Intelligence Scale (RAIS) questionnaire and semi-structured interviews. Quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed using thematic analysis. The findings reveal a structural imbalance in teacher readiness. While teachers demonstrate high levels of technological self-efficacy in using AI, their ability to detect AI misuse and verify student authenticity remains limited. Teachers adopt adaptive strategies such as restricting device use, implementing oral verification, and repositioning AI as a supportive tool rather than a substitute. These findings imply that teacher readiness is multidimensional and develops unevenly, highlighting the need for assessment redesign, ethical governance, and institutional support to maintain academic integrity in AI-mediated learning environments.